(untitled) (Bangladesh Journal of Botany, 2023)
Low temperature stress is one of the important environmental factor affecting the growth and development of wheat. As a widely existing hormone, salicylic acid do not only improve the immunity of wheat, but also improve the cold resistance capability of wheat. In the present study, effects of foliar spray of 0.3 g/l Salicylic acid (SA) on the cold resistance of wheat were studied under low temperature stress condition. Results showed that exogenous salicylic acid could enhance the activity of wheat antioxidant enzymes, reduce the content of Malondialdehyde (MDA) and change its own starch and sucrose synthesis, amino acid synthesis, carbon metabolism and glycolysis by affecting the differential expression of different hormone signal transduction genes and thereby improving the cold resistance of wheat. Bangladesh J. Bot. 52(2): 419-427, 2023 (June)